Corpos que romperam o silêncio e (res) significaram uma experiência: o teatro na formação inicial de professoras - Zanella, Andrisa Kemel (2008)
This work fits on the research line Professional Formation, Knowledge and Development and has as an objective to investigate some representations that college students of daytime Pedagogy Course had in relation to theater both before and after they experience the theatrical language in the subjects Theatrical Game I and Theatrical Game II. The choice for this thematic emerged from experiences lived throughout my formation of Bachelor of Drama Acting Course besides my interest in working with theater inserted in educational contexts. Such an interest get me to know and also teach a lesson in the subject Theatrical Game in Pedagogy Course, asking me to search how the living with theatrical language happens in a course that forms pedagogy professionals. Not only curiosity, but also the significations this experience proportioned to the teachers formation and also to the college students viewpoint in relation to theater were essential factors on the idealization and concretization of this study, which was created specifically to be developed in the subject Theatrical Game. To research about representations college students had in relation to theater was an opportunity to know which imaginary was instituted throughout their formation and which instituted possibilities have emerged from their experience in the subjects mentioned above. To do that, it was developed a methodological way that contemplates this problematic. Thus, the research, of qualitative features, was divided into six moments: group to be observed selection; participative observation; intervention in the subject Theatrical Game I and selection of four people to participate in the research; semi-structured interview; observation in the subject Theatrical Game II; structured written interview and finally data analysis. This diversity of instruments proportioned a reconstitution of the participants life history in relation to theater throughout their school period, besides accompanying the subjects Theatrical Game I and II, analyzing reflections and significations that college students attributed to theater during the living practice in the subject, knowing some significations about what, in their point of view, signify Theater for Education, as well as raising some possibilities of transformation occurred about the representations people had in relation to theater before and after the living practice. In involving myself into an investigation that tried to value the signification universe that permeates human relations, it was not my intention to establish truths or even do generalizations from an only context, but to have in mind that the reached results came from a lived process in a determined space limited by two important elements: time and space. Throughout this research, it was possible to perceive that the experience in the subject Theatrical Game I and Theatrical Game II operated in the previous representation that the future teachers had brought in relation to theater. This transformation was due to the meeting of what was known with the new perspectives, making possible, in this way, to interrupt the imaginary that was instituted to emerge an instituted imaginary that revealed another possibility to personal and professional developments as well as teachers formation.